Strategic performance measurement system, organisational capabilities and organisation competitive advantage: using levers of control framework / Rapiah Mohamed - Mohamed, Rapiah (2011)
The aim of this study is to examine the relationship between strategic performance measurement system (SPMS) and organisational competitive advantage. This study focuses on the choices of SPMS measures and how top management teams use the information provided by SPMS. Previous studies have examined the effect of SPMS separately, either by looking into SPMS design or SPMS use with little evidence concerning the simultaneously effect of SPMS design and use. There is also scant empirical evidence regarding the effects of SPMS design and use on competitive advantage using the levers of control framework and resource-based view (RBV) theory. This study extends prior research by examining the impact of SPMS on competitive advantage indirectly through the support of a beliefs and boundary control system and organisational capabilities. The conceptual model of this study is based on the levers of control framework and RBV theory. This study examines the moderating effect of the beliefs and boundary control system in the relationship between SPMS and organisational capabilities as well as the mediating effect of organisational capabilities in the link between SPMS and organisational competitive advantage. The main research question addressed by this study is whether SPMS design and use enhance competitive advantage indirectly through the support of a beliefs and boundary control system and organisational capabilities. A total of 778 questionnaires were sent to companies listed on the Main Board and second Board of Bursa Malaysia. The number of usable questionnaires was 145 responses, yielding an 18.8 percent response rate. Interviews were also conducted to gain a more in-depth understanding of the empirical results. Based on multiple regression analysis, the results indicate that SPMS design and use is significantly related to organisational capabilities. The findings reveal that the relationship between SPMS design and use and organisational competitive advantage is not direct, however, SPMS has an impact on competitive advantage indirectly through its ability to enhance organisational capabilities. The findings also indicate that the beliefs and boundary control system can moderate the relationship between SPMS design and use and entrepreneurship and innovation. Overall, the study demonstrates the importance of SPMS as a strategic control tool that can be used to enhance organisational capabilities and competitive advantage. The findings contribute to the body of the knowledge by identifying the role of SPMS from the perspective of RBV theory and levers of control framework.